GPS tracking of free-roaming dogs and human spillover risk of Echinococcus granulosus in highly endemic Peru - Morucci, Katherine; Ortiz Cam, Lizzie; Diaz, Elvis W.; Porras-Cotrina, Guillermo; Bustos, Javier; Verastegui, Manuela; Gavidia, Cesar M.; Castillo-Neyra, Ricardo (Frontiers in Veterinary Science, 2025)
IntroductionCystic echinococcosis (CE), a neglected disease that results from infection with the larval stage of the Echinococcus granulosus sensu lato (s.l.) tapeworm, poses significant zoonotic risk to humans and is a persistent threat in developing agricultural communities around the world. While the prevalence of human CE in the central highlands of Peru has previously been estimated around 5–7%, true prevalence is likely higher given the protracted period of asymptomatic disease, reduced medical access of at-risk populations, increased contact between herders, livestock, and herding dogs, and poor understanding of local disease epidemiology. To beIer understand CE epidemiology in a highly endemic region of Peru, we studied the movement of free-roaming dogs in the community of Chanchayllo, Junin, Peru.MethodsWe performed copro-ELISA to identify E. granulosus s.l. positive dogs, tracked the ranging behavior and calculated home ranges of 19 owned, free-roaming dogs to understand the movement of the definitive host of E. granulosus s.l. on the landscape. Specifically, we investigated the spatial association between E. granulosus-infected dog home ranges and proximity to their owners’ houses and a local slaughterhouse.ResultsEchinococcus granulosus s.l. infection prevalence was alarmingly high in our canine population, with 85% positivity (binomial exact 95% CI: 62.1–96.8%). All dog home ranges overlapped with their owners’ households, and notably, even negative dog households overlapped with nearby positive dog home ranges.DiscussionThese data suggest that widespread environmental contamination of E. granulosus s.l. egg-containing feces may be a significant driver of locally elevated disease prevalence in human populations. We use our findings to understand the local disease ecology of CE in free roaming dogs, assess pillover risk, and guide future intervention strategies aimed at reducing human cases. Our findings suggest that existing trategies delivering anthelmintic drugs to individual households have the potential to reduce spillover of E. granulosus s.l.